Reconfiguration of PV modules: A tool to get the best compromise between maximization of the extracted power and minimization of localized heating phenomena. (15th November 2016) - Balato, Marco; Costanzo, Luigi; Vitelli, Massimo
Highlights: Contrasting needs: maximize extracted power & minimize localized heating phenomena. Localized heating phenomena lead to the premature failure of PV modules. Give up available energy today in order to gain greater amount of energy tomorrow. Identify the optimal configuration and operating point for getting the compromise. Techno-economic analysis: compared to MPPT a slower power derating means earn money. Abstract: Localized heating phenomena due to bypass diodes conduction and/or to hot spots of reverse biased cells unavoidably lead to the damage or to the premature failure of PV modules. Therefore a proper control of the array operating point, with the aim to avoid or to limit the above phenomena, can be beneficial in order to maximize the energy production of the PV array itself during its lifetime. The basic idea which is discussed in this paper is that the maximization of the extracted power, when it is obtained at the price of too severe thermal stresses, is to be avoided. It may be preferable to give up a part of the available energy today in order to gain greater amount of energy tomorrow. In this paper, with specific reference to the Series Parallel PV array architecture, it is shown that, by means of the reconfiguration of the PV modules connections and with the help of a proper objective function, it is possible to identify, in any operating condition, both the optimal array configuration and the associated optimal operating point that are able to lead to the maximization of the extracted energy during the whole PV array lifetime.